Investigation into the Antihypertensive Effects of Diosmetin and Its Underlying Vascular Mechanisms Using Rat Model - Taseer Ahmad; Adil Javed; Taous Khan; Yusuf S. Althobaiti; Aman Ullah; Farooq M. Almutairi; Abdul Jabbar Shah (MDPI AG, 2022)
Objective: Diosmetin is a flavonoid that is found in many important medicinal plants that have antihypertensive therapeutic potential. Diosmetin has been shown to have antiplatelet, anti-inflammatory and antioxidant properties, which suggests that it could be a potential candidate for use in antihypertensive therapy. Methods: In vivo and in vitro methods were used for our investigation into the antihypertensive effects of diosmetin. Results: Diosmetin significantly decreased the mean arterial pressure (MAP). The effects of diosmetin on the MAP and heart rate were more pronounced in hypertensive rats. To explore the involvement of the muscarinic receptors-linked NO pathway, Nω-nitro-L-arginine methyl ester (L-NAME) and atropine were pre-administered in vivo. The pretreatment with L-NAME did not significantly change the effects of diosmetin on the MAP by excluding the involvement of NO. Unlike L-NAME, the atropine pretreatment reduced the effects of diosmetin on the MAP, which demonstrated the role of the muscarinic receptors. In the in vitro study, diosmetin at lower concentrations produced endothelium-dependent and -independent (at higher concentrations) vasorelaxation, which was attenuated significantly by the presence of atropine and indomethacin but not L-NAME. Diosmetin was also tested for high K+-induced contractions. Diosmetin induced significant relaxation (similar to verapamil), which indicated its Ca2+ antagonistic effects. This was further confirmed by diosmetin shifting the CaCl2 CRCs toward the right due to its suppression of the maximum response. Diosmetin also suppressed phenylephrine peak formation, which indicated its antagonist effects on the release of Ca2+. Moreover, BaCl2 significantly inhibited the effects of diosmetin, followed by 4-AP and TEA, which suggested that the K+ channels had a role as well. Conclusions: The obtained data showed the Ca2+ channel antagonism, potassium channel activation and antimuscarinic receptor-linked vasodilatory effects of diosmetin, which demonstrated its antihypertensive potential.